2002
DOI: 10.1002/art1.10239
|View full text |Cite
|
Sign up to set email alerts
|

Structural effect of avocado/soybean unsaponifiables on joint space loss in osteoarthritis of the hip

Abstract: Objective. To evaluate the structural effect of avocado/soybean unsaponifiables (ASU) in the treatment of patients with symptomatic osteoarthritis (OA) of the hip. Methods. Patients with regular painful primary OA of the hip (European League Against Rheumatism 1980 criteria) and a joint space still > 1 mm (Kellgren grade 1 to 3, assessed by an independent observer prior to inclusion) entered a prospective, multicenter, randomized, parallel group, double-blind, placebo-controlled trial of 2 years duration. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 25 publications
2
106
0
5
Order By: Relevance
“…There was no difference in clinical outcomes including pain or analgesic/non-steroidal antiinflammatory drug use (145) . This was somewhat similar to an earlier smaller study examining structural modification (146) , but very different from other earlier trials, where ASU demonstrated reductions in pain, functional disability or non-steroidal anti-inflammatory drug use in patients with hip or knee OA over 3-6 months (147)(148)(149) . In a dog anterior cruciate ligament transection model of OA, ASU reduced disease severity and decreased MMP13 production (150) , although in an ovine model of post-meniscectomy OA, ASU was described to have a 'subtle, but statistically significant' effect on cartilage (151) .…”
Section: Avocado-soyabean Unsaponifiablessupporting
confidence: 78%
“…There was no difference in clinical outcomes including pain or analgesic/non-steroidal antiinflammatory drug use (145) . This was somewhat similar to an earlier smaller study examining structural modification (146) , but very different from other earlier trials, where ASU demonstrated reductions in pain, functional disability or non-steroidal anti-inflammatory drug use in patients with hip or knee OA over 3-6 months (147)(148)(149) . In a dog anterior cruciate ligament transection model of OA, ASU reduced disease severity and decreased MMP13 production (150) , although in an ovine model of post-meniscectomy OA, ASU was described to have a 'subtle, but statistically significant' effect on cartilage (151) .…”
Section: Avocado-soyabean Unsaponifiablessupporting
confidence: 78%
“…In humans, ASU showed significant symptomatic efficacy in the treatment of OA [164]. Furthermore, one study evaluating the effect of ASU in hip OA patients over 2 years demonstrated a significant reduction in joint space loss in the most severe cases [165]. With regard to glucosamine, the hydrochloride formula administered to the cruciate transection rabbit OA model reduced the high subchondral trabecular bone turnover [166].…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%
“…ASU have been used in the management of OA as a nutraceutical agent. The symptomatic efficacy of ASU has been demonstrated recently in double-blind, placebo-controlled prospective clinical trials in patients with OA (Blotman et al 1997;Maheu et al 1998;Appelboom et al 2001), with an evidence of reduced joint space narrowing (Lequesne et al 2002). Its ability to protect the articular cartilage of osteoarthritic joints in vivo remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…They are manufactured in France, as Piascledine, and to our knowledge are distributed only in that country. ASU have a symptomatic effect on knee and hip OA and slow down joint space narrowing in severe hip OA (Maheu et al 1998;Appelboom et al 2001;Lequesne et al 2002;Ernst 2003). Two recent in vitro studies explored more extensively the potential mechanism of action of ASU in OA.…”
Section: Discussionmentioning
confidence: 99%